DRUG-INDUCED THROMBOCYTOPENIA - Suvajdžić-Vuković, Nada; Cvetković, Mirjana (Srpski medicinski časopis Lekarske komore, 2024)
Drugs could cause thrombocytopenia, mostly in hospitalized patients. The incidence of this adverse reaction to medicines is around 10/1,000,000 inhabitants/year. Depending on the pathophysiological mechanism, drug-induced thrombocytopenia can be classified into immune and non-immune. Drugs such as cytostatics, linezolid, ganciclovir, valacyclovir, aspirin, and vancomycin can induce a non-immune form of thrombocytopenia. They achieve this by exerting direct cytotoxic effects on megakaryocytes and platelets, or through proapoptotic mechanisms that affect platelets. On the other hand, the immune form is caused by drug-specific antibodies, which, in the presence of the drug or its metabolite, bind to platelet antigens, leading to accelerated destruction of platelets. Apart from this classic form of drug-induced immune thrombocytopenia (DITP), which is characterized by the acute onset of severe thrombocytopenia (nadir platelet counts < 20 x 109/L) and bleeding, special forms such as heparin-induced thrombocytopenia (HIT), thrombocytopenia caused by the use of immune checkpoint inhibitors, and vaccine-induced thrombotic thrombocytopenia (VITT) are identified. HIT is the most common DITP in which nadir platelet count is usually around 60x109/L and the clinical presentation is dominated by thrombosis (venous and less often arterial). Conversely, VITT is characterized by the onset of thrombosis and thrombocytopenia between 4 and 30 days after the administration of adenoviral vector vaccines. The mortality in this form of LITP ranges between 25% and 60%.